Kyai Authority in Nonformal Qur'anic Education: Enlivening The Qur'an, Interpretive Authority, and Religious Practice - Siti Fahimah; Lujeng Luthfiyah (Universitas Islam Negeri Sunan Kalijaga, 2026)
This article examines kyai authority in nonformal Qur'anic education by focusing on how religious leaders obtain and exercise interpretive authority through their capacity to enliven the Qur'an according to community needs in Pelangwot Village, Lamongan, East Java. The study addresses two research questions: (1) what are the forms of kyai authority in nonformal educational contexts? (2) why do these kyai obtain authority in their community? Employing a qualitative case-study design, the research gathered data through participant observation in TPQ learning sessions and mau'izhah forums, semi-structured interviews with teachers, kyai, and students, and analysis of institutional documents and teaching references. Data were analyzed using thematic coding to identify recurring patterns. Findings reveal two key dimensions. First, the forms of kyai authority in nonformal settings are predominantly socio-cultural, rooted in teacher-student transmission chains and community recognition rather than formal institutional structures. Kyai authority operates through teacher-student knowledge transmission, tolerates interpretive differences to maintain harmony, and remains fragmented across institutions. Second, kyai obtain their authority through the continuous labor of enlivening the Qur'an—selectively mobilizing established verses and hadith including